2019
DOI: 10.56093/ijans.v89i8.93024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding Hedge lucerne (Desmanthus virgatus) on intake, growth performance and body condition score in growing Osmanabadi goats

Abstract: An experiment was planned to explore the possibilities of replacement of concentrate mixture by Hedge lucerne (Desmanthus virgatus) in growing Osmanabadi goats for 90 days. Osmanabadi growing goats (18) of either sex with similar age and body weights (12.77±0.53 kg) were divided into two treatment groups and one control group (T0) with six goats in each group. Concentrate mixture was offered to control group (T0), while T1 and T2 groups received ration in which 50% and 100% concentrate was replaced by Hedge l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
1
1
Order By: Relevance
“…But the current result of CP digestibility was lower (63-87%) than Awoke [22], who supplemented Washera sheep with Ficus sycomorus Leaf, fruit, and their mixtures; Gezahegn [23] (73.0-81.0 %); and (76.0 %) [24]. While the current study's crude protein digestibility was comparable (62.0-79.0 %) [25], and the result was higher (56.8-60.9 %) [26]. The difference in digestibility between treatment groups could be due to the different feed compositions.…”
Section: Discussioncontrasting
confidence: 61%
“…But the current result of CP digestibility was lower (63-87%) than Awoke [22], who supplemented Washera sheep with Ficus sycomorus Leaf, fruit, and their mixtures; Gezahegn [23] (73.0-81.0 %); and (76.0 %) [24]. While the current study's crude protein digestibility was comparable (62.0-79.0 %) [25], and the result was higher (56.8-60.9 %) [26]. The difference in digestibility between treatment groups could be due to the different feed compositions.…”
Section: Discussioncontrasting
confidence: 61%
“…Radha Krishnan (2005) [9] showed the Madrared lamb fed with ration containing 60 percent of green fodder hay (T 1 ) and ration contained 60 percent of Neem: SS: GNH25:37.5:37.5, (T 3 ) Subabul: GNH:RS25:37.5:37.5 and (T 4 ) Gliricidia: GNH:RS 25:37.5:37.5 and recorded lower feeding cost per kilogram live weight gain in treatment groups as compare to control. Madhavi et al (2006) [8] [10] stated that the effect of feeding hedge lucerne (Desmanthus virgatus) at replacement of 50% and 100% concentrate mixture. They reported that total cost of production was significantly higher in control group T 1 than treatment group T 2 and T 3 and also found that the highest net profit per goat in T 2 group than other treatment.…”
Section: Economics Of Feedingmentioning
confidence: 99%